Produktivität und Effizienz in Banken: Terminologie, Methoden und Status quo - Andreas Burger (Frankfurt School of Finance & Management, 2008)
This Working Paper gives insights into the concepts of productivity and efficiency. Both concepts are popular measures for evaluating productive units, either on macro or micro level. This paper provides clear definitions for both concepts and outlines key areas of interest in this context, such as efficiency measures, components of efficiency and the appropriate levels for the analysis. On this basis the author introduces and discusses a selection of technical approaches for measuring productivity and efficiency in a non-technical manner. Various parametric as well as non parametric approaches are summarized. In addition, the two most popular efficiency measurement techniques, Stochastic Frontier Analysis (SFA) and Data Envelopment Analysis (DEA) are compared against each other. The current status of measuring productivity and efficiency in banking is discussed and results are summarized. Key findings from productivity and efficiency analyses for German banks are outlined. Furthermore the underlying models and assumptions in relation to efficiency measurement in banking are introduced and discussed. Finally it is proposed to increase the focus on analysing processes with respect to productivity and efficiency. This approach is providing an additional point of view and gives additional insights into the productivity and efficiency in banking.
urn:nbn:de:101:1-2008082974
Keywords: G21; L23; L25; M11; 330; Produktivität; Effizienz; Produktivitätsmessung; Effizienzmessung; data envelopment analysis; stochastic frontier analysis; Effizienz in Banken; Produktivität in Banken